A "living, cloven, apostolic tongue" and "philanthropic philology" – exploring the possibility of working-class writings on language theory in the 1840s. Issue 3 (2nd September 2018) - Cooper, Andrew
ABSTRACT: This article looks at two essays by John Goodwyn Barmby published in the New Moral World and Howitt's Journal of Literature and Popular Progress to explore the possibility of a working-class theory of language in England in the 1840s. Positioning these writings in relation to connections between politics, language theory and culture made by middle-class writers in the 1830s, I examine how they extend a tradition of "alternative" politically radical language theory from the turn of the century by invoking and accentuating discourses that became crucial to the study of language in England. I conclude that Barmby's essays are best understood as instances of working-class labour on language theory in the 1840s, and as such they provide an important critical perspective on the work being done by others to appropriate social, cultural and political discourses to define English language in terms of the emergent paradigm of the New Philology.